2020
DOI: 10.3389/fpsyg.2020.565153
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Economic Well-Being and Quality of Life of the Vietnamese During the National Social Distancing

Abstract: Starting from April 1st, 2020, the nationwide partial lockdown in Vietnam has shown the effectiveness in stopping the community transmission of COVID-19, however, it also produced adverse impacts on the economy and inhabitants' life. A cross-sectional study using a web-based approach was conducted in the second week of April 2020 to examine the influence of the national social distancing on the quality of life and economic well-being of Vietnamese citizens under COVID-19 pandemic. The data included socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
239
4
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(273 citation statements)
references
References 14 publications
19
239
4
11
Order By: Relevance
“…The financial impact of COVID-19 was assessed by asking, "How has your family's monthly income changed due to the impact of COVID-19?". There were three possible responses ⅰdecreased; (ⅱ) increased; (ⅲ) unchanged, as previously reported (Tran et al, 2020).…”
Section: Financial Impact Measurementioning
confidence: 54%
See 1 more Smart Citation
“…The financial impact of COVID-19 was assessed by asking, "How has your family's monthly income changed due to the impact of COVID-19?". There were three possible responses ⅰdecreased; (ⅱ) increased; (ⅲ) unchanged, as previously reported (Tran et al, 2020).…”
Section: Financial Impact Measurementioning
confidence: 54%
“…In the present study, 96.3% of respondents reported a decrease in their household income due to the impact of the COVID-19 pandemic. This rate is higher than those in Vietnam (66.9%) (Tran et al, 2020) and India (45.6%) (Keelery, 2020). The disparity could be attributable to differences in economic structures and major markets between countries.…”
Section: Discussionmentioning
confidence: 78%
“…15 The EQ-5D-5L has been validated in hundreds of countries and languages, providing a standardized approach to measure and compare health within and across nations. 15 Since the pandemic began, the EQ-5D-5L has been used to assess HRQoL in the Netherlands, 18 Germany, 19 France, 20 Morocco, 21 China, 22 Hong Kong, 23 Vietnam, 24 and Spain 25 in various contexts including the general public, those with speci c diseases, and healthcare providers; these studies have shown an overall decline in HRQoL, and pronounced worsening of anxiety and depression. The objective of this study was to assess the impact of COVID-19 on US population health using the EQ-5D-5L.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19, unlike the previous SARS disease, is markedly transmissible, necessitating swift and stricter interventions such as quarantining (1). Vietnam's broad response was successful in containing the spread of the virus, but poses considerations for subsequent precipitated mental health concerns specific to pandemic (responses) (18)(19)(20)(21)(22)(23)(24). Some studies of Vietnam have shown that social distancing and isolation measures can be associated with high rates of post-traumatic stress (20) and increased rates of depression/anxiety (24), especially those present in hospitals suspected of having COVID-19 symptoms (22).…”
Section: Considerations For Mental Healthmentioning
confidence: 99%
“…Vietnam's broad response was successful in containing the spread of the virus, but poses considerations for subsequent precipitated mental health concerns specific to pandemic (responses) (18)(19)(20)(21)(22)(23)(24). Some studies of Vietnam have shown that social distancing and isolation measures can be associated with high rates of post-traumatic stress (20) and increased rates of depression/anxiety (24), especially those present in hospitals suspected of having COVID-19 symptoms (22). Quarantining, which Vietnam has been aggressively employing, can impose psychological strain related to stigma, financial constraint, and guilt (18,19).…”
Section: Considerations For Mental Healthmentioning
confidence: 99%